Obstacle avoidance robot using sonar sensor (OARus) - Mohamad Sabri Abdullah
The main objectives of this project are to design and construct a "Obstacle Avoidance Robot Using Sonar (OARuS) Sensor" and to interface hardware and software using Embedded system.